2021
DOI: 10.48550/arxiv.2106.02961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-research on COVID-19: An overview of the early trends

Giovanni Colavizza

Abstract: COVID-19 is having a dramatic impact on research and researchers. The pandemic has underlined the severity of known challenges in research and surfaced new ones, but also accelerated the adoption of innovations and manifested new opportunities. This review considers early trends emerging from meta-research on COVID-19. In particular, it focuses on the following topics: i) mapping COVID-19 research; ii) data and machine learning; iii) research practices including open access and open data, reviewing, publishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…This focus centers on the transmission of important and life-saving health information to diverse audiences and the promotion and uptake of evidence-based public health measures to reduce virus transmission (e.g., proper hand washing, spatial distance, and mask-wearing). Examples were noted in traditional and nontraditional methods where Fraser et al [24] found that, as of October 2020, there were 125,000 scientific publications associated with COVID-19, and several that examined the increasing use and role of researchers and social media [25,26] as well as the importance of community-academic partnerships as a means for translating information [27].…”
Section: Introductionmentioning
confidence: 99%
“…This focus centers on the transmission of important and life-saving health information to diverse audiences and the promotion and uptake of evidence-based public health measures to reduce virus transmission (e.g., proper hand washing, spatial distance, and mask-wearing). Examples were noted in traditional and nontraditional methods where Fraser et al [24] found that, as of October 2020, there were 125,000 scientific publications associated with COVID-19, and several that examined the increasing use and role of researchers and social media [25,26] as well as the importance of community-academic partnerships as a means for translating information [27].…”
Section: Introductionmentioning
confidence: 99%